POTENSI ANTIOKSIDAN PADA BUAH LOKAL PAPUA - Martha Rumainum, Inna; Tuhumena, Veronica (Jurnal Teknologi Hasil Pertanian, 2018)
The aim of this article is to review the phytochemical compounds in three local fruits from Papua, i.e., redfruit, mahkota dewa and matoa, and to analyze their potential as antioxidant source. Fruit is known to containvarious beneficial nutrients. Antioxidant compounds that contained in fruit have important function againstcardiovascular diseases. Red fruit contains tocopherol and carotenoid compounds that actively act asantioxidant. Polyphenols that found in mahkota dewa and matoa also have important rules in free radicalsscavenging. These compounds have been demonstrated to suppress cancer cells in vitro.